Change in British society - Halsey, Albert H. 1923- (An Opus book, 1995)
In this lucidly argued book, A. H. Halsey offers a provocative analysis of the direction which British society has taken this century. He points to changes involving class and status, social and geographical mobility, standards of living, and the family, and explains how these changes have been affected by economic growth, liberal and Marxist theories, and the power of the state. This new and fully revised edition covers the whole of the twentieth century, including Margaret Thatcher's period as Prime Minister, and the premiership of John Major. It incorporates a wide range of issues which have arisen in the past few years: changes in education, the fortunes of political parties, the tightening of immigration control, the decline of the manufacturing industry, and the challenge which the 1990s poses to the nuclear family. Professor Halsey considers the implications of these recent events, and asks what their effects have been on liberty, equality, social cohesion, and conflict.